2021
DOI: 10.3390/molecules26237070
|View full text |Cite
|
Sign up to set email alerts
|

The Applications of Nanotechnology in Crop Production

Abstract: With the frequent occurrence of extreme climate, global agriculture is confronted with unprecedented challenges, including increased food demand and a decline in crop production. Nanotechnology is a promising way to boost crop production, enhance crop tolerance and decrease the environmental pollution. In this review, we summarize the recent findings regarding innovative nanotechnology in crop production, which could help us respond to agricultural challenges. Nanotechnology, which involves the use of nanomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 126 publications
0
33
0
Order By: Relevance
“…In addition, carbon nanoparticle nanotubes of Au, SiO 2 , ZnO, and TiO 2 ameliorate the development of plants by enhancing elemental uptake and use of nutrients (Fraceto et al 2016 ). A recent study on different crops has also shown increased germination, seedling growth, physiological activity like photosynthetic activity and nitrogen metabolism, m-RNA expression, and some positive changes in gene expression, fostering their potential use in crop improvement (Liu et al 2021 ; Salem and Husen 2022 ). A previous study used Penicillium expansum to produce NPs, which presented the possible for the extracellular fusion of ZnO NP with a size range of 3.5–67.3 nm, while they used DLS and SEM–EDX to determine the size and elemental composition.…”
Section: Application Of Nanoparticlesmentioning
confidence: 99%
“…In addition, carbon nanoparticle nanotubes of Au, SiO 2 , ZnO, and TiO 2 ameliorate the development of plants by enhancing elemental uptake and use of nutrients (Fraceto et al 2016 ). A recent study on different crops has also shown increased germination, seedling growth, physiological activity like photosynthetic activity and nitrogen metabolism, m-RNA expression, and some positive changes in gene expression, fostering their potential use in crop improvement (Liu et al 2021 ; Salem and Husen 2022 ). A previous study used Penicillium expansum to produce NPs, which presented the possible for the extracellular fusion of ZnO NP with a size range of 3.5–67.3 nm, while they used DLS and SEM–EDX to determine the size and elemental composition.…”
Section: Application Of Nanoparticlesmentioning
confidence: 99%
“…Majority of earlier findings suggested that the conventional fertilizer use efficiency hardly exceeds 30-40% owing to leaching, run off, hydrolysis, drift, evaporation, microbial degradation and photolytic activity [63,64]. Nonetheless, nano-formulation of fertilizers increases their use efficiency due to high stability and higher absorption [28,29].…”
Section: Wheat Biomass and Yield Enhancementmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 6, 2023. ; https://doi.org/10.1101/2023.01.06.522993 doi: bioRxiv preprint particles would reduce soil and air pollution, while providing higher crop yields and nutrient uptake [28,29]. Further, application of Zn in various formulations, including NPs, assists in enrichment of edible plant parts in Zn, resulting in reduced hidden hunger and Zn malnutrition [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reviews have been published on the application of nanosensors in the plant sciences. Unlike this review, they are generally focused on the specific applications of nanotechnology, e.g., to agriculture [ 19 , 20 , 21 ] or plant pathogen detection [ 22 , 23 ], specific areas, e.g., in planta nanosensors [ 24 ], or more specific forms of nanomaterial, e.g., carbon nanotubes [ 25 ]. This review focuses on nanosensors and their applications in living plants, plant cells, plant tissues, and plant organelles.…”
Section: Introductionmentioning
confidence: 99%